Metal Mining - Drilling Blastholes at the Holden Mine with Percussion Drills and Tungsten Carbide Bits - Discussion - Elton A. Youngberg (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1950)
J. H. HEARDING, Jr.*—Extremely hard ferruginous chert (taconite) was encountered in driving a drift at the Fraser underground mine near Chisholm, Minn., on the Mesabi Iron Range. In order to get better results in drilling in this ground, it was decided to try tungsten carbide bits. In the beginning, 1½ in. tungsten carbide bits and 1 1/8 in. round-lugged alloy steel drill rods with "jack-stud" inserts were used. Considerable difficulty was encountered because the jack-stud became loose in the drill rods. Because there was not enough alloy steel drill rod on hand, we began to insert jack-studs in the ordinary high carbon drill rods and found, to our surprise, that there was less trouble with jack-studs working loose in these rods than there had been with the alloy steel rods. As a result, use of the alloy steel rods has been discontinued entirely. Under the heading "Drilling Procedures" the statement is made that all holes are started with detachable bits or conventional steel to prevent undue strain on the tungsten carbide bit inserts when collaring a hole on uneven ground. This practice was followed in our work originally for the same reason. It was soon found, however, that the holes could be started with the tungsten carbide without injuring the inserts if the drill operator was careful and did not give the drill too much air until the bit had a chance to seat itself in the rock. J. C. FRANZ*—In a discussion of other technical papers with reference to percussion drills and the use of carbide tungsten bits, it was my impression that the authors reported one of the first difficulties experienced with the use of standard, conventional percussion drills, was insert bit failures due to crushing of the bit inserts when the bits became dull. During the past few years, some of the rock drill manufacturers, I am told, have adopted an air drill for use with the carbide bits that have a lighter blow and faster rotation than the regular machine. This machine has been tested and the carbide bit failures have been considerably reduced. L. W. DUPUY†—The difficulties Mr. Youngberg mentions that were had with rod and coupling breakage call to mind similar troubles experienced at the Picacho mine in California near Yuma.6 The commercial couplings then available were found to be tempered almost to brittleness. Rod breakage was usually in the threads near the end of the rod. The highly-tempered couplings would break as soon as the rod broke. The solution was to thoroughly anneal the couplings and to put in only a very mild temper. Subsequently the alloy used in making the couplings was changed from the original by the manufacturer, but still only a very mild temper was used. The result was that the softer coupling would give but would not snap and release its hold on the broken rod thread. Fishing jobs were reduced to the few where the rods broke at the rod end of the thread. Thread breakage on the rods was further reduced by thorough annealing prior to tempering. The data Mr. Youngberg presents regarding the use of carbide inserts on long blasthole drilling is most interesting and it would appear that the use in this manner of percussion drills and carbide bits will have many applications. W. M. WOODWARD*—How many feet of hole, on the average, do you get from a tungsten carbide bit, and is there much variation from this average? E. A. YOUNGBERG (author's reply) —In recent months the 2 in. tungsten carbide bit footages in long hole drilling hake varied from 115 .to 140 ft monthly. The footages obtained from individual bits vary from several feet to over 300 ft, however the life of a majority of the bits will be within 25 ft of the average.